The eighteenth data release of the sloan digital sky surveys: targeting and first spectra from SDSS-V - Almeida, Andrés; Anderson, Scott F.; Argudo-Fernández, Maria; Badenes, Carles; Barger, Kat; Barrera-Ballesteros, Jorge K.; Bender, Chad F.; Benitez, Erika; Besser, Felipe; Bird, Jonathan C.; Bizyaev, Dmitry; Blanton, Michael R.; et al. (The astrophysical journal. Supplement series)
The eighteenth data release (DR18) of the Sloan Digital Sky Survey (SDSS) is the first one for SDSS-V, the fifth generation of the survey. SDSS-V comprises three primary scientific programs or “Mappers”: the Milky Way Mapper (MWM), the Black Hole Mapper (BHM), and the Local Volume Mapper. This data release contains extensive targeting information for the two multiobject spectroscopy programs (MWM and BHM), including input catalogs and selection functions for their numerous scientific objectives. We describe the production of the targeting databases and their calibration and scientifically focused components. DR18 also includes ∼25,000 new SDSS spectra and supplemental information for X-ray sources identified by eROSITA in its eFEDS field. We present updates to some of the SDSS software pipelines and preview changes anticipated for DR19. We also describe three value-added catalogs (VACs) based on SDSS-IV data that have been published since DR17, and one VAC based on the SDSS-V data in the eFEDS field.